2022
DOI: 10.1096/fj.202200825r
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA‐EWSAT1promotes hepatocellular carcinoma metastasis via activation of theSrc‐YAPsignaling axis

Abstract: Regardless of the improvements in diagnostic and therapeutic methods, the clinical outcomes of hepatocellular carcinoma (HCC) patients remain poor. Although accumulating evidence indicates that lncRNAs (long noncoding RNAs) are essential within the control of tumorigenesis and the metastasis of cancer, the underlying mechanisms remain largely unknown. This work explored the pattern of expression and functional significance of a newly found lncRNA, Ewing sarcoma-associated transcript 1 (EWSAT1), in HCC metastas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Knockdown of EWSAT1, an important lncRNA, dramatically suppressed colony formation in soft anger in Ewing sarcoma (A673, SKNMC and TC71) cells(28). The functions of EWSAT1 were subsequently con rmed in other malignant tumors, such as ovarian cancer, hepatocellular carcinoma, colorectal cancer, and cervical cancer (32,33,45,46). In hepatocellular carcinoma, EWSAT1 was signi cantly upregulated compared with that in normal tissue and correlated with an aggressive phenotype and low overall survival.…”
Section: Discussionmentioning
confidence: 97%
“…Knockdown of EWSAT1, an important lncRNA, dramatically suppressed colony formation in soft anger in Ewing sarcoma (A673, SKNMC and TC71) cells(28). The functions of EWSAT1 were subsequently con rmed in other malignant tumors, such as ovarian cancer, hepatocellular carcinoma, colorectal cancer, and cervical cancer (32,33,45,46). In hepatocellular carcinoma, EWSAT1 was signi cantly upregulated compared with that in normal tissue and correlated with an aggressive phenotype and low overall survival.…”
Section: Discussionmentioning
confidence: 97%
“…EWSAT1 has been reported to play a pro-tumor role in a variety of cancers. EWSAT1 can contribute to the proliferation and invasion of glioma ( 63 ), promote HCC metastasis ( 64 ), and promote the progression of ovarian cancer ( 65 ). Studies on EWSAT1 in CRC have also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…[79] When the Hippo/YAP signaling pathway is activated, Yes-associated protein (YAP) promotes YAP phosphorylation induced by the sarcoma gene (Src) and further promotes nuclear translocation of YAP, so as to complete transcription against Hippo-YAP signaling target genes involved in cancer evolution. [80] In addition, triplet osteoprotegerin (OPG), receptor activator (RANK) and ligand RANKL that promotes tumor proliferation are also closely related to the occurrence and development of OS. RANKL secreted by tumor cells can bind to receptor RANK on the surface of osteoclasts and promote osteoclasts to differentiate into mature type.…”
Section: Nf-κb Signaling Pathwaymentioning
confidence: 99%